From Novice to Expert: Building Copyright Expertise Over Time - Savage, Stephanie (Journal of Copyright in Education & Librarianship, 2022)
Students and early career professionals should not be dissuaded from considering a career in copyright librarianship if they have an interest in the subject matter and a willingness to seek out professional development opportunities. Despite starting my MLIS degree with no legal or academic libraries experience, I was able to obtain a skill set in copyright literacy that enabled me to secure an entry level copyright librarian position upon graduation. Those who are willing to embrace being a novice and seek out available opportunities to build their expertise will find copyright librarianship a rewarding and valuable area of specialization to pursue.